Reducing Consumptive Behavior in Adolescents Through Increased Inhibitory Control - Jauhari, Hadi; Junianto, Mahmud; Nugraha, Yoga Aji; Lestari, Ayu; Anggraini, Nadiem; Haqqi, Asyrof (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Uncontrolled consumptive behavior can lead to wasteful lifestyles and poor financial decision-making abilities. The purpose of this study is to design a game media based on the teachings of neng ning nung nang, test the effectiveness of the game book to increase inhibitory control as an effort to reduce consumptive behavior, and analyze the differences in inhibitory control levels before and after using the developed game book. This study uses a quantitative method with the RnD approach. The RnD approach refers to the concept of Richey and Klein which consists of 3 stages, namely the development stage, internal validity testing, and external validity testing. Testing the effectiveness of the game media uses a quasi-experimental method. This study uses a game-based intervention conducted at SMK Negeri South Sumatra with 25 subjects selected using a purposive sampling technique. Research data collection uses observations and tests designed to determine differences in inhibitory control and in research subjects. The collected data will be analyzed using a paired sample t-test. The results of the study indicate that the designed game book is feasible to be implemented, the game book media is proven to be effective in reducing inhibitory control, and there are significant differences before and after the intervention using the game book.Perilaku konsumtif jika tidak dikontrol dapat membawa dampak pada gaya hidup boros dan kemampuan membuat keputusan finansial yang buruk. Tujuan penelitian ini adalah merancang media permainan bebrasis ajaran neng ning nung nang, menguji efektifitas buku permainan untuk meningkatkan inhibitory control sebagai Upaya menurunkan perilaku konsumtif, dan menganalisis perbedaan tingkat inhibitory control sebelum dan sesudah menggunakan buku permainan yang dikembangkan. Penelitian ini menggunakan metode kuantitatif dengan pendekatan RnD. Pendekatan RnD mengacu pada konsep Richey dan Klein yang terdiri dari 3 tahap, yaitu tahap pengembangan, uji validitas internal, dan uji validitas eksternal.  Pengujian efektifitas media permainan menggunakan metode kuasi eksperimen. Penelitian ini menggunakan game-based intervention yang dilakukan kepada SMK Negeri Sumatera Selatan dengan subjek sebanyak 25 orang yang dipilih menggunakan teknik purposive sampling. Pengumpulan data penelitian menggunakan observasi dan tes yang disusun untuk mengetahui perbedaan inhibitory control dan pada subjek penelitian. Data yang dikumpulkan akan dianalisis menggunakan sample paired t-test. Hasil penelitian menunjukan bahwa  buku permainan yang dirancang layak untuk diimplementasikan, media buku permainan terbukti efektif untuk menurunkan inhibitory control, dan terdapat perbedaan yang signifikan sebelum dan sesudah dilakukan intervensi menggunakan buku permainan.